Aplikasi Metode Quality Function Deployment Dalam Pengembangan Produk Air Minum Kemasan - Alfredo Tutuhatunewa (Industrial Engineering Study Program, Pattimura University, 2010)
Targets which wish reached in this research are: determining attribute as basis for effort of repair of product of drinking water tidiness; knowing consumer opinion about quality of AISO drinking water of tidiness; knowing effort conducted by company of related to quality of product of drinking water tidiness. Research done by using method of Quality Function Deployment (QFD). Reached Results are: there are 7 attribute lionized by consumer and applicable to measure the quality of product of drinking water tidiness, that is: design tidiness, water clearness, the sense, easy to get the product, price, resilience and tidiness strength, and also resilience and strength of water. Quality of Product of drinking water of tidiness AISO have very gratifying, Effort priority conducted by company to increase the quality of product of drinking water of tidiness AISO of pursuant to House of Quality are: Guarantee that all production equipments worn in a state of really clean, Observing production process tightly to ascertain its hygiene, and also ensure that the water distribution equipments from well guaranteed raw material location also its hygiene